Reproductive history and risk of nasopharyngeal carcinoma: A population-based case–control study in southern China. (January 2019) - Feng, Rui-Mei; Chang, Ellen T.; Liu, Zhiwei; Liu, Qing; Cai, Yonglin; Zhang, Zhe; Chen, Guomin; Huang, Qi-Hong; Xie, Shang-Hang; Cao, Su-Mei; Zhang, Yu; Yun, Jingping; et al.
Highlights: This is the first study to assess the NPC risk associated with reproductive history. A history of pregnancy or delivery increased the NPC risk. NPC risk decreased with increasing time since menopause. Abstract: Objects: Nasopharyngeal carcinoma (NPC) incidence exhibits a remarkable sex disparity, with higher risk among males. Whether this pattern can be partly explained by female reproductive history is unclear. Methods: A population-based case–control study of NPC was conducted in southern China between 2010 and 2014, including 674 histopathologically verified female NPC cases and 690 female controls randomly selected from population-based registries. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using logistic regression after adjusting for potential confounders. Results: Women who had 3, 4, or ≥5 pregnancies compared with 2 pregnancies were at significantly increased risk for NPC (ORs 1.56, 1.45 and 1.88, respectively). History of deliveries was similarly associated with a greater risk of NPC. These positive associations were more prominent in women who were younger than 50 years, had less than 10 years of education, or were white-collar workers. Increasing time since menopause was associated with a diminished NPC risk ( P trend  = 0.010). Women more than 15 years after menopause had a 0.35-fold (95% CI: 0.16–0.75) NPC risk compared with those 0–3 years after menopause. Conclusion: Contrary to our hypothesis, a history of pregnancy or delivery increased the risk of NPC and the risk decreased with increasing time since menopause. However, the non-linear relationship and no consistent risk patterns across strata indicate that the observed associations are unlikely to be causal, and may at least partially be ascribed to residual confounding by socioeconomic factors.